A Mitochondria‐Targeted Photosensitizer Showing Improved Photodynamic Therapy Effects Under Hypoxia. Issue 34 (6th July 2016) - Lv, Wen; Zhang, Zhang; Zhang, Kenneth Yin; Yang, Huiran; Liu, Shujuan; Xu, Aqiang; Guo, Song; Zhao, Qiang; Huang, Wei
Abstract: Organelle‐targeted photosensitizers have been reported to be effective photodynamic therapy (PDT) agents. In this work, we designed and synthesized two iridium(III) complexes that specifically stain the mitochondria and lysosomes of living cells, respectively. Both complexes exhibited long‐lived phosphorescence, which is sensitive to oxygen quenching. The photocytotoxicity of the complexes was evaluated under normoxic and hypoxic conditions. The results showed that HeLa cells treated with the mitochondria‐targeted complex maintained a slower respiration rate, leading to a higher intracellular oxygen level under hypoxia. As a result, this complex exhibited an improved PDT effect compared to the lysosome‐targeted complex, especially under hypoxia conditions, suggestive of a higher practicable potential of mitochondria‐targeted PDT agents in cancer therapy. Abstract : Two Ir III complexes, Ir‐P(ph)3 and Ir‐alkyl, were designed and synthesized to evaluate the mitochondria‐ and lysosome‐targeted PDT effect under normoxic and hypoxic conditions. As Ir‐P(ph)3 ‐treated cells could maintain a relatively high mitochondrial oxygen content under hypoxia, the mitochondria‐targeted complex Ir‐P(ph)3 showed a superior PDT effect than lysosome‐targeted complex Ir‐alkyl.